Contribuições da epistemologia de Ludwik Fleck para a formação de professores em Educação do Campo: um estudo dos estilos de pensamento sobre o conceito de natureza - Márcia Maria Martins Parreiras (2018)
The present study analised the thought styles (TS) of the students from the Degree Course in Field Education, in the area of Life and Nature Sciences, from the Federal University of Minas Gerais (LECampo-CVN/FaE/UFMG) in relation to the word nature, using as theoretical references the Compared Epistemology by L. Fleck and the Political Ecology by K. Whiteside. Once it comes to methodology, data was built from the participant observation, field visit, use of questionnaries and the execution of focal groups. The sample universe was composed by ten students from the mentioned course, divided into distinct groups, according to the thought collectives (TC) in which they move and/or moved. This way, the first group was composed by students coming from schools that valued the peasant culture; who exercised and/or exercise militancy in Campesino Social Movements and, moreover, whose fathers and/or mothers were peasants. The second group, in turn, was formed by students who had no insertions in any of those collectives, in such a way that the only similarity between both groups was the time spent at the LECampo. The analysis of the information shared by the students was made according to Semiotic and Content Analysis Movements. From the obtained results, there could be noticed a prevalence, in the first group, of CP over the nature of the centered anthropocentric clarified character, at the same time it could be identified the emergency of what we here believe turned into a new PE not centered, which we name as collective nature. In relation to the second group, it was noticed the presence of either the anthropocentric centered PE as well as the not centered PE, being the latter oriented to the humanist and systemic categories. Such delineations seem to be related to these students transit in distinct TC. This way, those participants from the first group who moved around through TC which valued the peasants way of life and lived practical and theoretical experiences for that matter, showed more critical positions in relation to the utilitarian idea of nature elaborated by the Modernity. The students from the second group, in turn, having moved around for only three years in a TC which advocated conceptions of non centered nature (in this case, the LECampo) and, at the same time, experiences which were sharply anthropocentric experimented through at least eight years, in the Primary Education, showed peculiar comprehension about the term. We argumented about the knowledge of such thought styles and about the importance of the LECampo and of the other TC at hand to confirm them, bring elements which contribute to the intercultural formation of teachers. Thats because they allow a better comprehension of the ontologies which guide the ways of life and the peasants fights, at the same time they illuminate keen domination mechanisms to which they are subject. Moreover, they give arguments to the Academy discussions about the socio-environmental problems and ways to minimize them.